Accounting and Finance Professionals’ Perception on The Current State of The Accountancy Profession in South Africa - MDHLULI, Sithandiwe; MKHIZE, Msizi; PHESA, MASIBULELE (International Journal of Environmental, Sustainability, and Social Science, 2023)
Accountants, auditors, and other finance professionals have traditionally been well respected and held in high regard by the public. They are regarded as financial reporting overseers because they are responsible for ensuring that organisations follow relevant regulations and financial laws. Globally, accounting and finance professions have been tarnished by scandals involving intentional manipulation of financial information. The professional ethics of finance professionals are under scrutiny by the concerned public at large. This study is informed by the repercussions of these scandals and how they have influenced the public view of the profession. The quantitative approach was adopted, using systematic sampling. 165 accounting and finance professionals at government, corporate institutions and audit firms were considered. An anonymous online questionnaire was the instrument used for the collection of data. Majority of accountants and finance professionals agree are in consensus that they perceive themselves to have a strong knowledge of ethics. Further, also perceive their fellow accounting and finance professionals to be ethically responsible. Additionally, being a member of professional accounting body influences the ethical behaviour and professional conduct of accounting and finance professionals. Worth noting, considerable accountants and finance professionals face a substantial amount of pressure to compromise on ethics The study adds to the debate on the perception of accountants and finance professionals from their perspective. Further, ascertain the role that professional bodies play to nurture professionals be to inclined to ethical behavior so as to maintain positive perception about them and the profession.